2016
DOI: 10.1016/j.jand.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and Behavioral Factors Associated with Added Sugars Intake among US Adults

Abstract: Background Reducing added sugars intake is one of the Healthy People 2020 objectives. High added sugars intake may be associated with adverse health consequences. Objective This cross-sectional study identified sociodemographic and behavioral characteristics associated with added sugars intake among US adults (18 years and older) using the 2010 National Health Interview Survey data (n=24,967). Methods The outcome variable was added sugars intake from foods and beverages using scoring algorithms to convert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
37
5
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 27 publications
12
37
5
2
Order By: Relevance
“…Further, in present study when it is observed the total of the countries the difference in SEL were observed only for total sugar intake, being the higher intake observed among those with the highest socioeconomic strata. This finding was the opposite seen in US adults studied by Park et al [ 23 ]. This can reflect different tax incentives to decrease added sugar consumption, which permits the acquisition of items that have more sugar by individuals of distinct SEL.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…Further, in present study when it is observed the total of the countries the difference in SEL were observed only for total sugar intake, being the higher intake observed among those with the highest socioeconomic strata. This finding was the opposite seen in US adults studied by Park et al [ 23 ]. This can reflect different tax incentives to decrease added sugar consumption, which permits the acquisition of items that have more sugar by individuals of distinct SEL.…”
Section: Discussioncontrasting
confidence: 76%
“…In present study, as demonstrated elsewhere [ 7 , 9 , 23 , 24 ], in absolute terms men showed higher sugar intakes than women; however, in relative terms this observation was the opposite, which reflects the greater energy intake by men inherent in their constitution that demands greater energy needs. In contrast, higher relative values in women demonstrate that they are consuming a more nutritionally unbalanced diet, at least as far as sugar intake is concerned, and it is still shown in studies investigating sugar-intake trends that the decline in sugar intake is lower in women compared to men [ 7 , 9 ].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Young adults are also among the greatest consumers of sugar-sweetened beverages (SSB) ( Dietary Guidelines Advisory Committee, 2015 ), which account for almost half of all added sugars consumed by the U.S. population ( U.S. Department of Health and Human Services and U.S. Department of Agriculture, 2016 ). High SSB intake in young adults is strongly associated with race, education, and economic factors ( Han and Powell, 2013 ; Park et al, 2016a , Park et al, 2016b ), has been shown to vary by geographic location ( Park et al, 2016a , Park et al, 2016b ), and to be associated with other high-risk behaviors such as low physical activity ( Kristal et al, 2015 ; Park et al, 2016a , Park et al, 2016b ), smoking ( Kristal et al, 2015 ; Park et al, 2016a , Park et al, 2016b ), and alcohol intake ( Park et al, 2016a , Park et al, 2016b ). Soda is the most heavily consumed SSB by young adults ( Han and Powell, 2013 ).…”
Section: Introductionmentioning
confidence: 99%